Pengaruh Literasi dan Return Terhadap Minat Mahasiswa Berinvestasi - Fatah, Mohammad Syaifullah; Na'im, Jannatun (IAIN Surakarta, 2020)
The purpose of this study was to determine the effect of investment literacy and investment return on the interests of FEBI S1 Islamic Economics Study Program students at IAIN Kudus in investing in the Islamic capital market. The design of this study is quantitative. The study population was all undergraduate students of FEBI ES Study Program IAIN Kudus. A sample of 100 respondents were selected using the purposive sampling method. The data is processed using SPSS for Windows version 23 application. The results of this study indicate that literacy and return partially affect the interest in investing in the S1 FEBI ES Study Program students at IAIN Kudus, as evidenced by the probability value of 0,000 <0.05. Literacy and return simultaneously influence the interest in investing in FEBI S1 ES Study Program students at IAIN Kudus, as evidenced by a Fcount of 27,027 and a probability of 0,000. Literacy and return affect investment interest by 35.8%, while the remaining 64.2% is influenced by other variables not explained in this study. Keywords: Literation, Returns, and Investment Interest